ISLAM DAN KONTROVERSI : ANALISIS SEMIOTIKA PADA POSTER FILM KIBLAT/THAGHUT - Khairi, Miftahul (UNIVERSITAS NUSA PUTRA, 2025)
Posters serve as a crucial component in media culture, acting as effective promotional tools. In promotional contexts, posters create images that captivate the public, encouraging them to respond and even engage with the advertised product. This study delves into the analysis of a film poster that sparked controversy in 2024, initially titled Kiblat and later renamed Thaghut. The primary issue addressed in this research is the semiotic analysis of the Kiblat/Thaghut film poster, examining the myths within the second-order sign system and exploring how these myths function as significant promotional media in media culture. The study employs Roland Barthes' semiotic theory, specifically his second-order sign system analysis, combined with Edmund Burke Feldman's basic design theory. A qualitative approach with a case study methodology is utilized, drawing data from visual materials of the poster and documents from the production house, Leo Pictures.The findings indicate that the Kiblat/Thaghut film poster displays religious symbols in a provocative manner, such as depicting a prayer scene facing the wrong direction. In the second-order sign analysis, the concept presented is